TEACHING ENGLISH IN EARLY CHILDHOOD EDUCATION IN INDONESIA: WHAT’S MISSING AND HOW TO FIX IT - Widya Rizky Pratiwi; Juhana; Nazirah Md Yusof; Joanne Echalico Bermillo; Maulina (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2026)
Early childhood education lays the foundation for lifelong learning by fostering essential competencies such as language acquisition, which is critical for cognitive, linguistic, and socio-emotional development. This study explores the constraints teachers face in implementing English language education in Early Childhood Education Institutions (ECE) across Indonesia and the support systems that can help bridge existing resource gaps. The research employs a qualitative case study design involving 17 institutions selected through purposive sampling. Data were collected through questionnaires, semi-structured interviews, and document analysis, focusing on the challenges, teaching practices, and institutional support systems. The study revealed that teachers faced significant barriers, including limited resources, insufficient training, and lack of institutional support, which hindered effective English language instruction. However, positive influences from professional development opportunities, government policies, and collaborative efforts were identified as key factors in overcoming these challenges. The study recommends enhancing teacher training programs, improving resource allocation, and strengthening institutional policies to support English language education in early childhood settings in Indonesia.